The Role of Invasion Status and Taxon of Basibionts in Marine Community Structure - Lazzeri, Kate; Auker, Linda A. (Frontiers in Ecology and Evolution, 2022)
Studies on nonnative epibionts typically focus on the organismal-level impacts of epibiosis on basibionts, rather than community-level impacts of this relationship. The purpose of our study was to evaluate if nonnative basibionts in general facilitate invasions through epibiosis in Maine compared to native basibiont species. We collected 64 basibiont assemblages including replicate samples of 10 different basibiont taxa on the central Maine coast in October 2019. Each basibiont and associated epibionts were identified to genus, classified as native or nonnative to the region where they were collected, and weighed. We found that while there was no association between invasion status of the epibiont and the basibiont, native basibionts had a significantly higher Shannon Diversity Index than nonnative basibionts. Although diversity of epibionts was greater on native basibionts, the percentage of invaders varied across basibiont taxa. Specific basibiont taxon characteristics may be more important than status because different taxa have different surface topographies, resulting in varying settlement among epibiont species. Our study indicates that there is differential settlement of epibiont taxa across basibiont taxa, which may help predict, based on surface characteristics, which species support more epibiont taxa. This study, as a snapshot of floating dock fouling communities within a 10km radius, may indicate that nonnative basibionts play a role in changing community structure. Expanding the scope of this initial study to include a wider taxonomic and geographic range should help determine if epibiosis is truly a facilitative process in invasions.